Acute toxicity outcomes and dosimetric implications from incidental irradiation of adjacent tissues in tangent field hypofractionated breast radiotherapy - Alcorn, Sara R. (Rep Pract Oncol Radiother, 2020)
PURPOSE: Adjacent tissues-in-beam (TIB) may receive substantial incidental doses within standard tangent fields during hypofractioned whole breast irradiation (HF-WBI). To characterize the impact of dose to TIB, we analyzed dosimetric parameters of TIB and associated acute toxicity. MATERIALS AND METHODS: Plans prescribed to 40.5 Gy/15 fractions from 4/2016-1/2018 were evaluated. Structures of interest were contoured: (1) TIB: all tissues encompassed by plan 30% isodose lines, (2) breast, (3) non-breast TIB (nTIB): TIB minus contoured breast. Volumes of TIB, breast, and nTIB receiving 100%–107% of prescription dose (V100-V107) were calculated. Twelve patient- and physician-reported acute toxicities were prospectively collected weekly. Correlations between volumetric and dosimetric parameters were assessed. Uni- and multivariable logistic regressions evaluated toxicity grade changes as a function of TIB, breast, and nTIB V100-V107 (in cm(3)). RESULTS: We evaluated 137 plans. Breast volume was positively correlated with nTIB and nTIB V100 (rho = 0.52, rho = 0.30, respectively, both p < 0.001). V107 > 2 cm(3) were noted in 14% of breast and 21% of nTIB volumes. On multivariable analyses, increasing breast and nTIB V100 significantly raised odds of grade 2+ dermatitis and burning/twinging pain, respectively; increasing nTIB V105 elevated odds of hyperpigmentation and burning pain; and increasing nTIB V107 raised odds of burning pain. Threshold volumes for >6-fold odds of developing burning pain were TIB V105 > 100 cm(3) and V107 > 5 cm(3). CONCLUSIONS: For HF-WBI, doses to nTIB over the prescription predicted acute toxicities independent of breast doses. These data support inclusion of TIB as a region of interest in treatment planning and protocol design